2007
DOI: 10.1007/s11661-007-9170-1
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ and Real-Time Investigation of Columnar-to-Equiaxed Transition in Metallic Alloy

Abstract: In this article, we present a review of observations during Al-3.5 wt pct Ni alloy solidification experiments performed at the European Synchrotron Radiation Facility (ESRF) in Grenoble. These experiments provide direct access to dynamical phenomena during columnar growth (initial transient and breakdown of a planar solid-liquid interface), and for the first time to the transition from columnar-to-equiaxed microstructure (nucleation ahead of a columnar front and blocking of a columnar front by an equiaxed micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
46
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 22 publications
10
46
0
Order By: Relevance
“…Over the last decade, an increasing number of real-time X-ray imaging studies of solidification microstructures and phenomena in real metals have been reported, addressing a broad variety of topics such as dendritic growth, [20][21][22][23] coarsening, [24] morphological transitions, [23] dendrite fragmentation, [25][26][27] solute diffusion and convection, [22,28] and momentum transfer relations in eutectics [29] and monotectics. [30] Most of these, and other recent in-situ studies, have been carried out with high-brilliance synchrotron radiation, where X-ray absorption-and near-field phase contrast is combined to bring about 2-D or 3D time-resolved data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, an increasing number of real-time X-ray imaging studies of solidification microstructures and phenomena in real metals have been reported, addressing a broad variety of topics such as dendritic growth, [20][21][22][23] coarsening, [24] morphological transitions, [23] dendrite fragmentation, [25][26][27] solute diffusion and convection, [22,28] and momentum transfer relations in eutectics [29] and monotectics. [30] Most of these, and other recent in-situ studies, have been carried out with high-brilliance synchrotron radiation, where X-ray absorption-and near-field phase contrast is combined to bring about 2-D or 3D time-resolved data.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Most of these, and other recent in-situ studies, have been carried out with high-brilliance synchrotron radiation, where X-ray absorption-and near-field phase contrast is combined to bring about 2-D or 3D time-resolved data. [20][21][22][23][24][25][26][27]29,30] …”
Section: Introductionmentioning
confidence: 99%
“…Under dynamical interaction with gravity-driven or forced fluid flow, localization of dendritic mush often establishes, and coupled growth with eutectic pattern is frequent, with dendrites protruding ahead into the liquid. 8) In casting, columnar dendrites are in practice in competition with the growth of equiaxed crystals. As on the one hand columnar dendrites with oriented mechanical properties are required.…”
Section: Columnar Dendritic Growth Columnar-toequiaxed Transition Anmentioning
confidence: 99%
“…[2][3][4][5][6] Critical growth phenomena and stress-driven effects in dendritic solidification and equiaxed growth of Al-based alloys were observed and characterized using the experimental set-up combining Synchrotron XRay Radiography (SXRR) and Synchrotron White-Beam X-Ray Topography (SWBXRT) that we have developed at the European Synchrotron Radiation Facility (ESRF). [7][8][9] This set-up and the experimental procedure we use are first briefly described. Then, selected typical observations of dynamical phenomena of major importance in microstructure formation or/and having significant effect on grain structure are shown.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) In general, the final microstructures of the casting are the result of the competition between the growth of an outer columnar (oriented properties) and an inner equiaxed (isotropic properties) grains. 3) Traditionally, most previous studies of the microstructure have relied on the post-solidification, optically transparent materials and computer simulation. These research tools have supplied valuable insight toward understanding alloy solidification.…”
Section: Introductionmentioning
confidence: 99%